Revitalisasi Nilai-nilai Tauhid dalam Pendidikan Islam Digital: Telaah Teoritis dan Praktis melalui Kecerdasan Buatan - Umayyatun (ISEDU : Islamic Education Journal, 2025)
Digital transformation in Islamic education demands a new approach that integrates the values of monotheism with modern technology. This research aims to explore the revitalization of monotheistic values through digital Islamic education by utilizing artificial intelligence (AI). The study employs a qualitative approach with a literature review from 2020 to 2025. The results show that AI can serve as an educational aid in internalizing monotheistic values, whether through learning chatbots, Islamic content recommendation systems, or digital behavior analysis of students. However, ethical and methodological challenges need to be anticipated through a curriculum framework based on the maqashid shariah. This research recommends a wise integration of AI with the principles of monotheism to create an adaptive Islamic education that remains rooted in divine values.Keywords: monotheism, digital Islamic education, artificial intelligence, maqashid shariah, technology ethics